Analisis Pengaruh Social Media Marketing Dan Kredibilitas Influencer Terhadap Keputusan Pembelian Dengan Kepercayaan Merek Sebagai Mediator: Studi Pada Pengguna Lipstik Wardah Di Kota Semarang - Arini Rizkia Nursukma; Imroatul Khasanah (Diponegoro Journal of Management, 2025)
The cosmetics industry, particularly in the real of lipstick products, is experiencing rapid growth due to an increasing consumer interest in beauty items. Social media and influencers have emerged as powerful marketing tools that significantly shape consumer preferences and purchasing decisions within this sector. However, the decline in popularity of the Wardah lipstick brand presents a challenge for the company in regarding customer loyalty amidst fierce competition. This study aims to analyze the extent to which social media marketing and influencer credibility impact purchasing decisions for Wardah lipstick products, while considering the role of brand trust as a mediating factor.This research employed purposive sampling to identify appropriate participants, specifically Wardah lipstick users in Semarang City. Data was gathered through an online survey administered via Google Forms, targeting respondents who met the set criteria. A total of 135 individuals completed the survey. The collected data was subsequently analyzed using the Structural Equation Model (SEM) approach, utilizing AMOS 24 software.The findings reveal that social media marketing strategies and influencer credibility have a significant positive effect on consumer trust in the Wardah brand. Furthermore, the study demonstrates that social media marketing, influencer credibility, and consumer trust in the brand collectively exert a positive and significant influence on the purchasing decisions related to Wardah lipstick products.